Section 6: Education and Consumer Informatics: Methods to Meet the Informational Demands of Patients and Health Professionals - Marschollek, Michael (Yearbook of Medical Informatics, 2006)
To summarize current excellent research in the field of education and consumer informatics.Synopsis of the articles selected for the IMIA Yearbook 2006.In the consumer informatics field current research focuses on meeting the informational needs of laypersons as well as health professionals with their specific demands and abilities. The selected papers’ topics are genetic diseases and conditions, decision support for women considering genetic testing for the risk of breast cancer, history taking and advice for parents with children suffering from asthma, timed messages to motivate and support quit smoking efforts and the integration of health economics in medical education.The selected articles demonstrate examples of excellent research in consumer health informatics and medical education. The methods presented can contribute to the development of systems for the education of both laypersons and health professionals.
Keywords: Medical Informatics; International Medical Informatics Association; Yearbook; Education; Consumer Health Informatics